2013
DOI: 10.1186/1471-2407-13-492
|View full text |Cite
|
Sign up to set email alerts
|

Selenized milk casein in the diet of BALB/c nude mice reduces growth of intramammary MCF-7 tumors

Abstract: BackgroundDietary selenium has the potential to reduce growth of mammary tumors. Increasing the Se content of cows’ milk proteins is a potentially effective means to increase Se intake in humans. We investigate the effects of selenized milk protein on human mammary tumor progression in immunodeficient BALB/c nude mice.MethodsFour isonitrogenous diets with selenium levels of 0.16, 0.51, 0.85 and 1.15 ppm were formulated by mixing low- and high-selenium milk casein isolates with a rodent premix. MCF-7 cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The increased cell proliferation in the mammary gland of the Se‐DEF female offspring could represent another mechanism underlying paternal programming of breast cancer risk. Se has been shown to exert cell cycle regulatory effects in breast cancer cells and breast tumor‐bearing animals . In maternal intervention studies Se deficiency altered the expression of cell cycle control genes in the offspring's colonic tissue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased cell proliferation in the mammary gland of the Se‐DEF female offspring could represent another mechanism underlying paternal programming of breast cancer risk. Se has been shown to exert cell cycle regulatory effects in breast cancer cells and breast tumor‐bearing animals . In maternal intervention studies Se deficiency altered the expression of cell cycle control genes in the offspring's colonic tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Se has been shown to exert cell cycle regulatory effects in breast cancer cells and breast tumor-bearing animals. 40,41 In maternal intervention studies Se deficiency altered the expression of cell cycle control genes in the offspring's colonic tissue. 21 On the other hand, the observation of decreased apoptosis in both Se-DEF and Se-SUP female offspring mammary glands suggests that this cellular process is not directly linked to increased breast cancer risk in the former group.…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed preclinical studies showed an inverse relationship between circulating levels of Se and vascular epithelial growth factor (VEGF) [78]. Se supplementation seemed to inhibit tumor progression in preclinical studies and cell cultures [79]. A decrease in Se levels appears to be widespread in cancer progression, but there is no evidence of its benefits as an adjuvant in tumor progression.…”
Section: Seleniummentioning
confidence: 99%
“…The increased cell proliferation in the mammary gland of the Se-DEF female offspring could represent another mechanism underlying paternal programming of breast cancer risk. Se has been shown to exert cell cycle regulatory effects in breast cancer cells and breast tumor bearing animals [40,41]. In maternal intervention studies…”
Section: Discussionmentioning
confidence: 99%
“…As most of selenoproteins exerts antioxidant activity, it was proposed that increased Se status could protect DNA against oxidative damage (Moghadaszadeh & Beggs 2006) Concerning breast cancer, interest was increased because of initial studies showing that Se status in blood and nails was lower in breast cancer patients than in healthy subjects (Männistö et al, 2000;Rejali et al, 2007) and some epidemiological studies showed a correlation between Se status and breast cancer risk . (Ip, 1981;Thompson et al, 1982;Thompson et al, 1989) and mice supplementation with organic/inorganic Se or selenized milk casein decreased growth of intramammary tumors (Chen et al, 2013;Warrington et al, 2013).…”
Section: Selenium and Breast Cancermentioning
confidence: 99%